Primary analysis of the trajektory of floating particles in compound channel - Marcin Krukowski; Piotr Siwicki (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The aim of the study was to determine the parameters of the stream transport capacity using turbulent diffusion coefficients using the imaging technique and to compare them with the coefficients obtained as a result of the measurement with the ADV (acoustic Doppler velocimeter) probe in a compound channel.